Cardiovascular outcomes of patients with rheumatoid arthritis prescribed disease modifying anti-rheumatic drugs: a review. Issue 7 (3rd July 2018) - Giollo, Alessandro; Bissell, Lesley-Anne; Buch, Maya H.
ABSTRACT: Introduction : Rheumatoid arthritis (RA) is associated with a heightened risk of cardiovascular disease (CVD), with both traditional CV risk factors and inflammation contributing to this risk. Areas covered : This review highlights the burden of CVD in RA and associated traditional CV risk factors, including the complexity of dyslipidemia in RA and the so-called 'lipid paradox.' Furthermore, the recognized RA-disease-specific factors associated with higher risk of CVD and the role of systemic inflammation in the pathogenesis of CVD in RA will be addressed. With the advent of biologic and targeted synthetic therapies in the treatment of RA, the effect of conventional and newer generation disease modifying anti-rheumatic therapies (DMARDs) on CV risk and associated risk factors will also be discussed. Expert opinion : Identifying the RA phenotype at greatest risk of CVD, understanding the interplay of increased traditional risk factors, common inflammatory processes and RA-specific factors, and personalized use of DMARDs according to disease phenotype and comorbidity to reduce this risk are key areas for future research.